Construction and characterisation of a Semliki Forest virus vector based rubella prototype vaccine - Callagy, Sara Jane (Trinity College (Dublin, Ireland). Department of Microbiology, 2007)
Alphavirus vaccines such as those based on the Semliki Forest virus (SFV) replicon have been widely studied as candidate vaccines. Following intramuscular injection, dispersal of the RNA occurs to the local lymph node only, persisting only for 7 days. Recombinant SFV (rSFV) particles are suicidal and undergo only one round of multiplication, killing the cells by apoptosis induction. Replication of RNA is entirely cytoplasmic thus there is no possibility of insertional mutagenesis. Vaccination against rubella is contra-indicated in pregnant women or those considering pregnancy because of the risk of infection of the developing foetus, and such women therefore remain at risk of infection with the wild-type virus and consequent congenital rubella syndrome in the infant after birth.
Keywords: Microbiology, Ph.D.; Ph.D. Trinity College Dublin